HARTA SEPENCARIAN DAN WANG SIMPANAN KWSP: SUATU PERBINCANGAN DARI SUDUT "SUMBANGAN SECARA TIDAK LANGSUNG" - Tapah, Suwaid (Jurnal Syariah, 2019)
The claim and distribution of Harta Sepencarian (couple's property jointly acquired during marriage) in Shariah Courts is a"common practice among Muslims in Malaysia. This article discusses the terms of "a direct and indirect contribution" pertaining to harta sepencarian as stated by the Islamic Family Law in some states and the decisions made by Shariah Courts. However, there is an arising issue with regard to whether the spouse can claim the Employee Provident Fund as harta sepencarian based on the interpretation of "indirect contribution" if one of them earns some money as "a defined contribution". Therefore, this article tries to analyze that issue based on some relevant provisions of Islamic Family Law and some reported cases.